The Concept of New Women Reflected in Nayantara Sahgal’s The Day in Shadow - Dr. P. Jeyappriya (International Journal of Advanced Science and Technology, 2020)
Nayantara Sahgal has raised her voices for female upliftment in all her works. They must enjoy not only the physical freedom but also the mental freedom because for the physical violence women facing, law will come forward to support her but for the inner violence she has to fight by herself. Sahgal presents one such bold woman, Simrit in her novel, The Day in Shadow. To a woman emotional security is more important than social security, whereas a man thinks that a woman needs only material comforts, for her emotions and sentiments are very important. Thus there is a conflict between the material and emotional happiness. Sahgal clearly pictures the misery, economic difficulties, feeling of loneliness and innumerable other problems confront the protagonist, Simrit. The novel is pre-occupied with domestic tragedy of Simrit who ultimately seeks divorce through a ruthless divorce document prepared by her husband. The separation has shattered the life of a woman in the society which gives too much value for marriage and its relations. The main objective this article to study the female protagonist Simrit on the new woman theory. This theory states that the female can have full freedom to lead her life.